Pietro Antonio Solari’s Sculpture in the Light of the Latest Research - Aleshin, Pavel A. (Actual Problems of Theory and History of Art, 2023)
Until the early 2010s, only two sculptures were mentioned in connection with Pietro Antonio Solari — the Madonna del Coazzone from the Castello Sforzesco in Milan and the tomb of Bishop Marco de Capitani from the Cathedral of Alessandria. The main question, which still remains open, is their stylistic inconsistency with each other. Both works confirm the generally accepted opinion that Solari was not an outstanding sculptor and his manner was rather archaic for the last quarter of the 15th century. However, recent studies by Vito Zani (2011) and Ann Markham Schultz (2013) have linked several other sculptural works to Pietro Antonio Solari. The analysis of these works and the new information regarding Madonna del Coazzone and the tomb of Bishop Marco de Capitani have allowed the author to raise a number of new questions and to expand the context in which the work of the master in the field of sculpture should be studied.
Keywords: Pietro Antonio Solari; Renaissance; art of Lombardy; Quattrocento; sculpture